1991
DOI: 10.1002/jcp.1041490214
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction by bFGF, but not TGFβ1, involves arachidonic acid metabolism in endothelial cells

Abstract: We investigated the stimulation of early cellular events resulting from the interaction of the growth factor basic FGF (bFGF) and of the growth inhibitor transforming growth factor beta-type 1 (TGF beta 1), with their specific receptors on bovine endothelial cells. At mitogenic concentrations, bFGF stimulated the rapid release of arachidonic acid and its metabolites from (3H)-arachidonic acid labeled cells. When arachidonic acid metabolism was stimulated by addition of the calcium ionophore A23187, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 40 publications
5
41
0
Order By: Relevance
“…AA, preferentially through its metabolites, plays a key role in different phases of the angiogenic process, including endothelial cell proliferation (38)(39)(40). We previously showed that AA promotes cell proliferation in bovine aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…AA, preferentially through its metabolites, plays a key role in different phases of the angiogenic process, including endothelial cell proliferation (38)(39)(40). We previously showed that AA promotes cell proliferation in bovine aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid and its metabolites are involved in the regulation of a variety of physiological processes including vascular tone (23,24). In addition, these lipid molecules have been reported to mediate intracellular signaling events in response to a number of stimulants (25)(26)(27)(28)(29)(30). A large body of data also suggests that arachidonic acid and its metabolites play an important role in cell survival and proliferation (31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Arachidonic acid and its metabolites, known as eicosanoids, are involved in the regulation of a variety of biological processes including vascular tone (5,6). In addition, these lipid molecules have been reported to mediate intracellular signaling events in response to a number of stimuli (7)(8)(9)(10)(11)(12). A large body of pharmacological data suggests that arachidonic acid and its eicosanoid metabolites stimulate mitogenesis in various cell types, including cancer cells (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%